First-in-Human Evaluation of the Safety and Immunogenicity of a Recombinant Vesicular Stomatitis Virus Human Immunodeficiency Virus-1 gag Vaccine (HVTN 090). (5th June 2015) - Fuchs, Jonathan D.; Frank, Ian; Elizaga, Marnie L.; Allen, Mary; Frahm, Nicole; Kochar, Nidhi; Li, Sue; Edupuganti, Srilatha; Kalams, Spyros A.; Tomaras, Georgia D.; Sheets, Rebecca; Pensiero, Michael; et al.
Abstract: Background. We report the first-in-human safety and immunogenicity evaluation of a highly attenuated, replication-competent recombinant vesicular stomatitis virus (rVSV) human immunodeficiency virus (HIV)-1 vaccine. Methods. Sixty healthy, HIV-1-uninfected adults were enrolled in a randomized, double-blinded, placebo-controlled dose-escalation study. Groups of 12 participants received rVSV HIV-1 gag vaccine at 5 dose levels (4.6 × 10 3 to 3.4 × 10 7 particle forming units) (N = 10/group) or placebo (N = 2/group), delivered intramuscularly as bilateral injections at 0 and 2 months. Safety monitoring included VSV cultures from blood, urine, saliva, and swabs of oral lesions. Vesicular stomatitis virus-neutralizing antibodies, T-cell immunogenicity, and HIV-1 specific binding antibodies were assessed. Results. Local and systemic reactogenicity symptoms were mild to moderate and increased with dose. No severe reactogenicity or product-related serious adverse events were reported, and all rVSV cultures were negative. All vaccine recipients became seropositive for VSV after 2 vaccinations. gag -specific T-cell responses were detected in 63% of participants by interferon-γ enzyme-linked immunospot at the highest dose post boost. Conclusions. An attenuated replication-competent rVSV gag vaccine has an acceptable safety profile in healthy adults. This rVSV vector is a promising new vaccine platform for the development of vaccines to combat HIV-1 and other serious human diseases.